2016
DOI: 10.1039/c5cp03092g
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase synthesis of Mg–Ti nanoparticles for solid-state hydrogen storage

Abstract: Mg-Ti nanostructured samples with different Ti contents were prepared via compaction of nanoparticles grown by inert gas condensation with independent Mg and Ti vapour sources. The growth set-up offered the option to perform in situ hydrogen absorption before compaction. Structural and morphological characterisation was carried out by X-ray diffraction, energy dispersive spectroscopy and electron microscopy. The formation of an extended metastable solid solution of Ti in hcp Mg was detected up to 15 at% Ti in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
5
28
1
Order By: Relevance
“…The inspection of TEM images indeed reveal a small NPs diameter dNP14nm in samples A and B (14 and 22 at.% Ti, respectively), dNP10nm in sample C (46 at.% Ti) and dNP7nm in sample D (63 at.% Ti). The decreasing NPs diameter with increasing Ti content (see Table ) is consistent with our previous studies ,. In sample A with the smallest Ti content, TEM analysis spots the presence of larger particles with a diameter of 50 nm (see Figure S3 of the SI).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The inspection of TEM images indeed reveal a small NPs diameter dNP14nm in samples A and B (14 and 22 at.% Ti, respectively), dNP10nm in sample C (46 at.% Ti) and dNP7nm in sample D (63 at.% Ti). The decreasing NPs diameter with increasing Ti content (see Table ) is consistent with our previous studies ,. In sample A with the smallest Ti content, TEM analysis spots the presence of larger particles with a diameter of 50 nm (see Figure S3 of the SI).…”
Section: Resultsmentioning
confidence: 83%
“…In sample A with the smallest Ti content, TEM analysis spots the presence of larger particles with a diameter of 50 nm (see Figure S3 of the SI). Particles of this size are not present in as‐synthesized Mg‐Ti‐H NPs ,. This means that coarsening phenomena take place during hydrogen cycling, likely coupled with the structural rearrangements and volume changes that accompany the metal‐hydride transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to the case of surfaces discussed above, grain boundaries between nanocrystals contain excess energy, resulting in surface energy, thus providing another potential tool for reducing the formation enthalpy of metal hydrides. Calizzi et al 56 prepared Mg-Ti nanostructured samples with a metastable Mg-Ti-H fcc phase and the mean crystallite size of Mg and b-MgH 2 decreased with an increase in Ti content (Fig. 13).…”
Section: Nanostructuringmentioning
confidence: 99%
“…The combination of high surface area, small particle size and nanoscale dispersion of TiH 2 made it possible to measure equilibrium and kinetic properties of the Mg/MgH 2 system down to 70 • C without using Pd as capping or catalyst layer [48]. Prior to hydride formation, the NPs consisted in a hcp metastable Mg-Ti solid solution up to~15 at.% Ti, as demonstrated by high resolution elemental mapping (Figure 13b) and X-ray diffraction [89]. Krishnan et al also observed that bimetallic Mg-Ti NPs grown by gas-phase condensation have better thermal stability against void formation (Nanoscale Kirkendall effect) and Mg evaporation [95].…”
Section: Mg-ti Nanomaterialsmentioning
confidence: 99%